Intermediate downshifted maximum of stimulated electromagnetic emission at high‐power HF heating: A new twist on an old problem. Issue 1 (15th January 2015) - Grach, S. M.; Sergeev, E. N.; Mishin, E. V.; Shindin, A. V.; McCarrick, M.
Abstract We report a new spectral feature of Stimulated Electromagnetic Emission (SEE) from the F region ionosphere observed during high‐power HF heating experiments at the SURA and High Frequency Active Auroral Research Program heating facilities. It is located in the SEE spectrum between the pump wave frequency f0 and the well‐known Downshifted Maximum and thus named the Intermediate Downshifted Maximum (IDM). IDM appears at effective radiated powers (ERP) P0<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3xcxgmpb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />≳</alternatives>30 MW and the pump frequencies above electron gyroharmonics, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3xcxgmm7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />f0−sfce≳50</alternatives> (up to 250) kHz (s = 2, 3, 4). It mirrors the well‐known Upshifted Maximum (UM) relative to f0. The salient stationary and dynamic properties of IDM are described and discussed.